S131 Identifying Occupational Asthma Among a Cohort of Cleaners in the North East England. (19th November 2012) - Alfajjam, S; Stenton, C; Pless-mulloli, T; Howel, D
Abstract : Introduction: We have demonstrated a prevalence of asthma of 14% in a survey of 1400 UK hospital and university cleaners, and an estimated incidence of asthma of 3.3/1000 person-years. 26% of cleaners reported work-related symptoms. We have explored the possibility that these cleaners have occupational asthma using serial measurements peak expiratory flow (PEF) and airway responsiveness. Objectives: To identify occupational asthma in a cohort of cleaners. Methods: A respiratory symptom questionnaire was distributed among 1400 cleaners working in three local hospital trusts and two universities. Airway responsiveness (PD20) was measured in those with asthma symptoms using a methacholine challenge test. Those with measurable airway responsiveness (PD20 <1600ug) were invited to undergo a repeat measurement away from work and to carry out serial PEF measurements that were analysed for a work-related effect using OASYS (Burge, Pantin et al. 1999). Results: 557 (40%) returned the questionnaire and 167 reported respiratory symptoms. Of these, 56 (33.5%) attended for methacholine challenge testing. 26 (46%) had quantifiable results. 12 subjects underwent serial PD20 measurements at and away from work. Overall, there were no significant changes in airway responsiveness. Geometric mean PD20 at work was 193 ug and away from work was 254 ug (t=0.6; p=0.5). 5 cleaners showed a 3-fold or more increase in PD20 away from work raising the possibility of significant changes in those individuals. 10 subjects completed serial peak expiratory flow measurements. The mean OASYS score was 1.97. One subject had a score of > 2.5 suggesting a work related effect. Conclusion: Although the prevalence of asthma symptoms in our cohort is consistent with other epidemiological evidence showing a 1.5 to 2.0 fold risk of asthma, we found little evidence of occupational asthma using conventional clinical diagnostic tests in this group. The findings are consistent with the hypothesis that cleaners develop their asthma in an unusual way, possibly though a low dose irritant mechanism. Burge, P.S., C.F.A. Pantin, et al. (1999). "Development of an expert system for the interpretation of serial peak expiratory flow measurements in the diagnosis of occupational asthma." Occupational and Environmental Medicine 56 (11): 758–764.